2021
DOI: 10.1161/atvbaha.120.315773
|View full text |Cite
|
Sign up to set email alerts
|

Shear and Integrin Outside-In Signaling Activate NADPH-Oxidase 2 to Promote Platelet Activation

Abstract: Objective: Despite the importance of reactive oxygen species (ROS) and NOX (nicotinamide adenine dinucleotide phosphate [NADPH] oxidase) 2 in platelet activation and in vivo thrombosis, it is unclear how ROS and NOX2 play a role in platelet activation and why NOX2 deficiencies in humans and mice do not affect hemostasis. Outside-in signaling of integrin α IIb β 3 mediates platelet response to shear stress, secondary platelet act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
10
1
Order By: Relevance
“…Overall, the underlying mechanisms for the inhibitory effect of RA on Aβ 1–40 -induced platelet adhesion may involve inhibition of NADPH oxidase/ROS/PKC-δ/integrin α IIb β 3 signaling. Although reports have previously indicated a relationship between NADPH oxidase and integrin α IIb β 3 activity in platelets [ 7 , 41 ], this However, the present study is the first to reveal a link between NADPH oxidase/PKC-δ and Aβ 1–40 -induced integrin α IIb β 3 in the process of platelet adhesion. Our study further showed that RA inhibits all these signaling pathways, consequently inhibiting platelet adhesion.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Overall, the underlying mechanisms for the inhibitory effect of RA on Aβ 1–40 -induced platelet adhesion may involve inhibition of NADPH oxidase/ROS/PKC-δ/integrin α IIb β 3 signaling. Although reports have previously indicated a relationship between NADPH oxidase and integrin α IIb β 3 activity in platelets [ 7 , 41 ], this However, the present study is the first to reveal a link between NADPH oxidase/PKC-δ and Aβ 1–40 -induced integrin α IIb β 3 in the process of platelet adhesion. Our study further showed that RA inhibits all these signaling pathways, consequently inhibiting platelet adhesion.…”
Section: Discussioncontrasting
confidence: 65%
“…Platelets are key cells that play a critical role in vascular pathology via thrombogenic activity, as well as by adhering to damaged vessels [ 1 , 7 , 8 ]. Recent studies have indicated a possible role of platelets in the pathology of vascular dementia and AD, given that platelets contain amyloid precursor proteins (APP) and α-, β-, and γ-secretases, which contribute to the production of circulating Aβ [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under low shear rate perfusion in normal physiology (such as venous flow), platelets interact with adsorbed fibrinogen and collagen via their glycoprotein VI (GPVI) receptors. The integrin α IIb β 3 (also known as GPIIb/IIIa) located on platelet membranes enhances the arrest of free platelets onto immobilised fibrinogen (Savage et al, 1998;Maxwell et al, 2016;Xu et al, 2021) (Figure 5). The strong integrin α IIb β 3 -fibrinogen interaction guarantees a firm and immediate adhesion of the platelet on contact with the surface (Savage et al, 1996).…”
Section: Low-intermediate Shear Rate (< 1000 S -1 )mentioning
confidence: 99%
“…Note that GSK3β is also involved in the HIF-α subunit regulation ( Flugel et al, 2007 ) (Module Box I and Figures 2B,C ) and the axin-dependent YAP degradation and compartmentalization ( Azzolin et al, 2014 ) (Module Box V and Figure 4C ). The third is to act through niche mechanics- and ROS-interdependent integrin signaling ( Werner and Werb, 2002 ; Gregg et al, 2004 ; Buricchi et al, 2007 ; Taddei et al, 2007 ; Zeller et al, 2013 ; Xu Z. et al, 2021 ), where the activation of ILK potentiates Notch signaling ( Maydan et al, 2010 ) and regulates GSK3β activity ( Maydan et al, 2010 ).…”
Section: Main Textmentioning
confidence: 99%